Leveraging Zakat and Waqf for Public Health Improvement: Islamic Philanthropy’s Role in Addressing Stunting in Indonesia - Rizqi Anfanni Fahmi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study investigates the importance of Islamic philanthropy, particularly zakat and waqf, in combating child stunting in Indonesia. Islamic philanthropy can work as a long-term and effective way to reach this goal by combining ethical frameworks, institutional progress, and policies that have been proven to work in the real world. The study uses a narrative review method that is based on looking at history. The process entails methodically gathering literature from the Scopus database utilizing Boolean search strings such as Islamic Philanthropy, Stunting AND Indonesia, Zakat, and Waqf. The findings indicate that Islamic social finance has transitioned from traditional charitable donations to a system focused on impact, integrating religious principles with national development objectives. Faith-based financing can help improve nutrition, sanitation, and maternal health outcomes, as shown by programs like Zakat Community Development and Cash Waqf Linked Sukuk. However, integrating Islamic philanthropy into public health frameworks encounters obstacles stemming from regulatory ambiguity, fragmented governance, and inadequate impact evaluation. The study stresses the importance of having standardized performance metrics, working together across sectors, and making progress in digital technology to make sure that developmental outcomes can be measured. This study fundamentally enriches both theoretical and practical comprehension of Islamic philanthropy, reconciling the intersection of religious obligation and enduring human advancement. It offers a culturally attuned approach to achieving health equity and social justice in Muslim-majority contexts.